(untitled) (Baghdad Science Journal, 2011)
The present study aimed to evaluate the concentration of Malon dialdehyde (MDA) in pregnant women during different stages of pregnancy (stage of pregnancy, abortion, contraceptives and parity number).The study included (120) blood samples from normal pregnant women in age of the procreating were subdivided into three trimesters of pregnancy (40/group), and (40) samples from non-pregnant women as a control group. The results showed a significant increase in MDA in three stages of pregnancy compared with the control group. The concentration of MDA increased significantly in pregnant women with multipregnancy when compared with pregnant women for the first time, and in pregnant women whom was using contraceptions compared with pregnant women whom weren’t using contraceptions, while there was non significant alternative in MDA level in pregnant women suffered from abortion compared with the pregnant women that didn’t aborted .